MORPHOLOGICAL CHARACTERIZATION OF SOME MEMBERS OF Ocimum L. (Lamiaceae) IN THE SOUTHWEST STATES OF NIGERIA - Akinyemi, Oluwaseun Faith; Ayodele, Muyiwa Segun; Ayo-John, Emily I. (FUDMA Journal of Sciences, 2024)
The genus Ocimum (Lamiaceae) is made up of aromatic plants that have economic and medicinal benefits but their taxonomy has been difficult. In tandem with this, are other plants with emission of strong fragrance, but not of the Ocimum group. Morphological studies were conducted on certain Ocimum species in the southwest states of Nigeria to hdelimit some members of the genus. From the six states in the Southwest Nigeria, the seeds of one hundred and twenty accessions belonging to Ocimum basilicum L. (B-accessions), O. canum L. (C- accessions) and O. gratissimum L. (G-accessions) were collected. In three replicates in a single row, the seeds of each accession were planted in plastic pots of 10 litre capacity, filled with topsoil. Forty-five accessions were purposively selected based on the rate of germination. Data was collected on the qualitative and quantitative characters from vegetative, floral and fruit (nutlets) features. Statistical analyses of the quantitative data were performed using SAS/PC1 version 9.01. The results separated the B-accessions early on and confirmed that they were not part of the Ocimum group. The B-accessions, however, belonged to another genus Hyptis in the family. Based on leaf shapes, leaf colour, leaf apices, leaf pubescence, inflorescence arrangement and flower colours, five distinct morpho-types of Ocimum, were observed. This study revealed the existence of morphological variations among the C-accessions. These characteristics may be explored by plant breeders and taxonomists for sustainable utilization of the Ocimum germplasm.